Lower Facial Height and Soft Tissue Changes in Bimaxillary Protrusion Cases - Kasmawaricin Kasmawaricin; Nurhayati Harahap; Amalia Oeripto (Faculty of Dentistry, Trisakti University, 2019)
Background: Bimaxillary protrusion is frequently treated by extracting the four first premolars and retracting the incisor with maximum anchorage. This treatment may result in soft tissue changes, particularly in lip retraction, lip thickness, upper lip angle and nasolabial angle. However, the changes in facial height after orthodontic treatment often trigger controversies. Objectives: To determine the effects of incisor retraction on lower facial height and soft tissue changes in Class I malocclusion with bimaxillary protrusion treated by the extraction of the four first premolars. Methods: Pre-treatment and post-treatment lateral cephalometric radiograph samples of 25 patients treated with the standard Edgewise fixed appliance were collected. Each sample was traced and a reference line perpendicular to Sella-Nasion minus 7º through the true vertical line (TVL) was established. Arnett analysis was applied to calculate incisor retraction, lower facial height, lip retraction, lip thickness, upper lip angle and nasolabial angle changes. The results of the measurements were statistically analyzed using a paired T-test and Pearson correlation. Results: No statistically significant changes were found between upper incisor retraction and lower facial height (p > 0.05) and upper lip thickness (p > 0.05). The same lower incisor retraction occurred with lower facial height (p > 0.05) and lower lip thickness (p > 0.05). Significant positive correlation was found between upper incisor retraction and the changes in the upper lip retraction (r = 0.959, p < 0.05), upper lip angle (r = 0.775, p < 0.05) and nasolabial angle (r = 0.647, p < 0.05), while the lower incisor retraction had a positive correlation with the changes in lower lip retraction (r = 0.902, p < 0.05). Conclusion: The extraction of the four first premolars followed by the retraction of the incisor can cause changes in lip retraction, upper lip angle and nasolabial angle but not in lower facial height and lip thickness.